Social Neuroscience: Promise and Caveats - Harmon-Jones, Eddie; Devine, Patricia G. (Journal of Personality & Social Psychology, 2003)
A special section on the promise and caveats of social neuroscience is presented. Topics discussed include the regulatory function of self-conscious emotion; whether self-enhancing cognitions are associated with healthy or unhealthy biological profiles; electrocortical measures of attention to the race and gender of multiply categorizable individuals; a social cognitive approach to the effects of alcohol perception; neural components of social evaluation; making sense of brain-imaging research within the fields of cognitive and social neuroscience; and what neuroimaging can do, cannot do, and should not do for social psychology. An introduction to the special section is also provided.